2019
DOI: 10.5005/jp-journals-10016-1177
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding as a Cause of Congenital Hydrocephalus

Abstract: Aim:The aim of the study was to determine the role of inbreeding in occurrence of lethal congenital hydrocephalus (LCH) and congenital abnormalities associated with it. Materials and methods: There was an examination of 182 fetuses born with LCH, out of which 69 were diagnosed with isolated and 113 fetuses were diagnosed with associated hydrocephalus resulting in 38% and 62% occurrences, respectively. All the fetuses were the result of spontaneous abortions, stillbirths, neonatal deaths and the pregnancy termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…21 Another study reported 25% cases of hydrocephalus due to first degree marriages. 22 Similar results were reported by another study where congenital hydrocephalus was observed in 38% consanguineous marriages. 23 Atrial diameter >10mm is labeled as ventriculomegaly whereas biparietal diameter is used to assess gestational age.…”
Section: Discussionsupporting
confidence: 86%
“…21 Another study reported 25% cases of hydrocephalus due to first degree marriages. 22 Similar results were reported by another study where congenital hydrocephalus was observed in 38% consanguineous marriages. 23 Atrial diameter >10mm is labeled as ventriculomegaly whereas biparietal diameter is used to assess gestational age.…”
Section: Discussionsupporting
confidence: 86%
“…Newborns with higher birth weight have a greater chance to survive. In their case the reduced costs are due to prevention of severe and chronic diseases 9 . The sooner the surfactant is applied in case of newborns RDS, the greater their survival chances are 10 .…”
Section: Introductionmentioning
confidence: 99%